Ambivalences of the social philosophy of Jean Baudrillard and Pierre Bourdieu - Garncarek, Tomasz (Hybris, 2016)
Jean Baudrillard and Pierre Bourdieu are two well known French social philosophers that have at least couple of things in common. They were born in the same social conditions, they grew up as rebels, and they participated in Revolution of 1968. They also participated in the very same formal problems of the research work. The problem is, what happens when one introduces same difficulties in one’s ideas as those, that he was searching to neutralize. Bourdieu criticizes the system of education, art, culture in general, because it contributes to reproduction and conservation of social hierarchy. However, he's doing it using quite similar kind of high developed concepts, that he had criticized before. Baudrillard also detests modern social habits. Most of all, so called hyperreality, that manifests itself as a lack of real connection between things and concepts or ideas related to them. Nonetheless Baudrillard seems to adore hyperreality also, as a dimension of game, seduction. Bourdieu, as well as Baudrillard, appears as an adept of pataphysics — according to the definition given to this notion by Baudrillard, based on novels of Alfred Jarry.